The roles of phenotypic plasticity and adaptation in morphology and performance of an invasive species in a novel habitat - Jardeleza, Marcel Kate Guarin, author; Hufbauer, Ruth A., advisor; Pearse, Ian S., committee member; Pejchar, Liba, committee member; Ghalambor, Cameron K., committee member (Colorado State University. Libraries, 2020)
Invasive species spread and thrive across widely variable habitats. Their success in novel environments may be influenced by phenotypic plasticity, which occurs when a genotype can produce multiple phenotypes in response to different environments, or local adaptation, the production of traits that are advantageous under the local environmental conditions regardless of their effects in other habitats. One indication of these non-mutually exclusive processes comes in the form of geographic or elevational clines in phenotypes and genotypes. Drosophilla suzukii is an outstanding example of an invasive species that has established across many diverse environments and exhibits an elevational cline in wing size. In my thesis, with collaborators Jonathan Koch, Ian Pearse, Cameron Ghalambor, and Ruth Hufbauer, I evaluated the degree to which plasticity and genetic differentiation determine differences in wing sizes, and whether plasticity appears to be adaptive or not. I first characterized an elevational cline in wing size in D. suzukii on Hawaii and also evaluated its relative abundance by elevation. I then conducted a reciprocal temperature experiment to understand the mechanisms driving the cline. We found that wing size increased with elevation and that D. suzukii was significantly more abundant in higher elevation sites compared to lower elevation sites. Temperature may be the key driver of wing size variation, with wing size increasing as temperature decreased along the elevational gradient. In the reciprocal temperature experiment, I found that temperature had a strong effect on development time and cooler temperatures took longer to emerge compared to warmer temperatures. The reciprocal temperature experiment further revealed strong phenotypic plasticity. When flies from high and low elevation were reared at a cool temperature comparable to that found at high elevation, they produced larger wings. When reared at a warm temperature comparable to that found at low elevation, they produced smaller wings, which is the same pattern of variation observed in field populations. Additionally, I found significant differences in the number of flies that emerged from the two experimental temperatures. Flies from low and high elevation sites produced similar numbers of offspring at the cool temperature, while high elevation flies produced significantly more offspring at the warm temperature compared to the low elevation flies, despite that temperature being their home temperature. My study revealed strong plasticity in wing size, but no indication of local adaptation. If the wing phenotypes observed in high and low elevation populations in the field represent fit phenotypes, then this plasticity is adaptive. The flies may be exhibiting an "all-purpose genotype" where a fit phenotype is produced across the environmental conditions and there is no selection for adaptation to occur. As evidence continues to mount in support of the highly plastic responses of D. suzukii to temperature, particularly with respect to wing size, and the possible adaptiveness of this response, future studies need to make the direct connection between wing plasticity and adaptation. How an invasive organism responds to different environments determines the extent of its novel range and the places that it will impact. Hawaiian populations of D. suzukii exhibit substantial phenotypic variation in wing size, development time, and offspring production with some genetic component to that plasticity.
Keywords: ecology; invasive species; temperature size rule; evolutionary ecology; Drosophila suzukii